Organocatalyzed synthesis of fluorinated poly(aryl thioethers) - Park, Nathaniel H.; Gomes, Gabriel dos Passos; Fevre, Mareva; Jones, Gavin O.; Alabugin, Igor V.; Hedrick, James L. (Nature communications, 2017)
The preparation of high-performance fluorinated poly(aryl thioethers) has received little attention compared to the corresponding poly(aryl ethers), despite the excellent physical properties displayed by many polysulfides. Herein, we report a highly efficient route to fluorinated poly(aryl thioethers) via an organocatalyzed nucleophilic aromatic substitution of silyl-protected dithiols. This approach requires low catalyst loadings, proceeds rapidly at room temperature, and is effective for many different perfluorinated or highly activated aryl monomers. Computational investigations of the reaction mechanism reveal an unexpected, concerted S N Ar mechanism, with the organocatalyst playing a critical, dual-activation role in facilitating the process. Not only does this remarkable reactivity enable rapid access to fluorinated poly(aryl thioethers), but also opens new avenues for the processing, fabrication, and functionalization of fluorinated materials with easy removal of the volatile catalyst and TMSF byproducts. Fluorinated poly(aryl thioethers), unlike their poly(aryl ethers) counterparts, have received little attention despite excellent physical properties displayed by many polysulfides. Here the authors show a highly efficient route to fluorinated poly(aryl thioethers) via an organocatalyzed nucleophilic aromatic substitution of silyl-protected dithiols.